Anthropogenic food resources foster the coexistence of distinct life history strategies: year‐round sedentary and migratory brown bears. (22nd June 2016) - Cozzi, G.; Chynoweth, M.; Kusak, J.; Çoban, E.; Çoban, A.; Ozgul, A.; Şekercioğlu, Ç. H.
Abstract: Plastic behavioral adaptation to human activities can result in the enhancement and establishment of distinct behavioral types within a population. Such inter‐individual behavioral variations, if unaccounted for, can lead to biases in our understanding of species' feeding habits, movement pattern and habitat selection. We tracked the movements of 16 adult brown bears in a small and isolated population in north‐east Turkey to (1) identify inter‐individual behavioral variations associated with the use of a garbage dump and (2) to examine how these variations influenced ranging patterns, movements behavior and habitat selection. We identified two remarkably distinct behavioral types: bears that regularly visited the dump and remained sedentary year‐round and bears that never visited the dump and migrated 165.7 ± 20.1 km (round‐trip mean cumulative distance ± se ) prior to hibernation to search for food. We demonstrated that during migratory trips, bears moved more rapidly and were less selective in habitat choice than during the sedentary phase; during the migration phase, forest cover was the only important environmental characteristic. Our results thus reinforce the growing evidence that animals' use of the landscape largely changes according to movement phase. Our study shows that anthropogenic food resources can influence food habits, which can have cascading effects on movement patterns and hence habitat selection, ultimately resulting in the establishment of distinct behavioral types within a population. Identification and consideration of these behavioral types is thus fundamental for the correct implementation of evidence‐based conservation strategies at the population level. Abstract : To cope with novel and constantly changing environments, cognitively complex species may develop plastic strategies, which can result in the establishment of distinct alternative behaviors and life history strategies within a population. We identified two remarkably distinct behavioral types: bears that regularly visited a garbage dump and remained sedentary year‐round and bears that never visited the dump and migrated 165.7 ± 20.1 km prior to hibernation to search for food. Our study shows that anthropogenic food resources can influence food habits, which can have cascading effects on movement patterns and hence habitat selection, ultimately resulting in the establishment of distinct behavioral types within a population. Identification and consideration of observed variation in behavioral types is fundamental for the correct implementation of evidence‐based conservation strategies. Failures to detect such differences could result in the erroneous allocation of limited conservation resources, such as setting aside portions of land characterized by landscape features that are critical to only particular behavioral types.